Orofacial pain disorders: An overview and diagnostic approach - Kuan-Po Peng; Thalea Oppermann (SAGE Publishing, 2022)
Background: Non-dental orofacial pain disorders are not uncommon, but idiopathic or primary facial pain syndromes are rare. Inadequate recognition of these disorders usually leads to unsatisfactory and unmet treatment needs. Methods: We conducted a narrative review with a literature search in PubMed until December 2021, focusing on current guidelines and the recently published International Classification of Orofacial Pain (ICOP). Results: In this paper, we provide an updated overview of the common orofacial pain disorders following the ICOP, covering the classification, epidemiology, pathophysiology, clinical approaches, and treatment options. Additionally, we propose a pragmatic approach focusing on the attack duration to improve distinguishing orofacial disorders. Conclusion: The introduction of ICOP offers the opportunity to better coordinate and concentrate scientific efforts, which lays the foundation for the identification of the disease mechanism of facial pain disorders and the optimization of the currently still insufficient therapeutic strategies.